Chemistry and Biological Activity of Coumarins at Molecular Level - Garro, Hugo Alejandro (2014)
Synthetic coumarins were prepared using ionic liquids as an environmental friendly alternative with high yields. The compounds 3,4-dimethyl-7-hydroxycoumarin (3ab) and 3-isopropyl-4-methyl-5,7-dihydroxycoumarin (3bc) have showed interesting activity against Taq DNA polymerase with IC50 values of 115.74 μM and 82.24 μM, respectively. Also, the compounds 4-methyl-7-hydroxycoumarin (3aa) and 4-methyl-5,7-dihydroxycoumarin (3ba) have exhibited inhibitory activity against MMLV-RT with IC50 values of 23.46 μM and 18.35 μM, respectively. These inhibitors could have importance as antiretroviral chemotherapeutic agents and also in the development of antitumor drugs.